Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/2515841420950846
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for central serous chorioretinopathy

Abstract: Central serous chorioretinopathy (CSCR) is a common chorioretinal disease characterized by serous retinal detachment that most commonly involves the macular region. Although the natural history of the acute form shows a self-limiting course, a significant number of patients suffer from recurrent episodes leading to chronic disease, often leaving patients with residual visual impairment. Visual morbidity is often worsened by a delay in the diagnosis due to the incorrect understanding of the particular biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…CSCR is associated with several risk factors and conditions, including systemic glucocorticosteroid use, male sex, high educational attainment, high income, smoking, Helicobacter pylori infection, stress, and hyperopia [7,8]. In addition, a previous study demonstrated that type-A personality, Cushing's syndrome, systemic hypertension, retinal vascular occlusive diseases, and obstructive sleep apnea may be associated with CSCR [1,2,[8][9][10][11]. e possible explanation for these associations is that elevated cortisol and epinephrine levels affect the choroidal circulation's autoregulation [9].…”
Section: Introductionmentioning
confidence: 99%
“…CSCR is associated with several risk factors and conditions, including systemic glucocorticosteroid use, male sex, high educational attainment, high income, smoking, Helicobacter pylori infection, stress, and hyperopia [7,8]. In addition, a previous study demonstrated that type-A personality, Cushing's syndrome, systemic hypertension, retinal vascular occlusive diseases, and obstructive sleep apnea may be associated with CSCR [1,2,[8][9][10][11]. e possible explanation for these associations is that elevated cortisol and epinephrine levels affect the choroidal circulation's autoregulation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Even its etiology and exact pathogenesis are not entirely understood. Choroidal changes play a major role, and CSCR is caused by leakage of fluid from the choroid due to increased choroidal vascular permeability (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Recently advanced Choroidal imaging techniques are essential for both the diagnosing and evaluation of treatment outcomes. Imaging biomarkers such as choroidal thickness, choroidal vascularity index, hyperreflective dots, which are quantifiable parameters, are fundamental for possible prognosis (1)(2)(3)(4)(5). Other several risk factors such as demographic and physiologic factors, lifestyle, and corticosteroid medication are the main predictive factors for the incidence of CSCR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations